A Study on Customer Preference and Problems on Retailing with Special Reference to Chennai City (International Journal of Scientific Research and Management (IJSRM), 2022)
India is set for high growth in consumer expenditure. With India’s large ‘young’ population and high domestic consumption, the macro trends for the sector look favorable. Within retail, the emerging sectors would be food and grocery, apparel, electronics, e-commerce, fashion and lifestyle. Incorporation of technology in the organized retail segment has been something to reckon with in the past few years. Use of computers for merchandise planning and management, control of inventory costs and supplies and replenishment of goods done electronically, internal store billing, etc. has changed the face of product retailing